Development and psychometric properties of the online health information-seeking skill scale - Fatemeh Sadat Izadi-Avanji; Jalal Hashemi-Demne; Mahboobeh Kafaei-Atrian (International Archives of Health Sciences, 2021)
Aims: Given the dearth of research about middle-aged people's ability to seek online health information in developing countries, this study was conducted to develop the Online Health Information-Seeking Skill Scale (OHI-SSS) and evaluate its psychometric properties. Materials and Methods: This is a methodological study in which a scale was developed within three factors and was validated by face validity, content validity, and structural validity methods. Four hundred and twenty middle-aged individuals completed the questionnaires. Internal consistency and test–retest were used to evaluate the reliability of the scale. Finding: The initial scale, consisting of 38 items on a 5-point Likert scale, was reduced to a 26-item scale following face and content validity measurement. The exploratory factor analysis extracted three subscales in OHIO-SSS that includes “information reception,” “provide and exchange information, and “identification and trust.” Internal consistency of the scale was confirmed by Cronbach's alpha coefficient (0.93). Cronbach's alpha coefficient for subscales was 0.87, 0.795, and 0.74, respectively. Reliability analysis with test–retest revealed an acceptable estimate for the total score (intraclass correlation coefficient = 0.92). Conclusion: The 20-item OHI-SSS has acceptable validity and reliability. Therefore, it can be employed as an appropriate instrument for the evaluation of middle-aged people's skills in seeking online health information.